CFR capacity assessment - Sean, Vichet; Ou, Phichong; Sun, Vathanak (WorldFish, 2024)
The CFR capacity assessment will be conducted using a tool was developed and utilized during the USAID funded Rice Field Fisheries project (see Kim et al., 2019). It will be conducted with CFR committees on an annual basis to assesses committee performance on five aspects of CFR management capacity: 1. Organization management ; 2. Planning and implementing the plan; 3. Resource mobilization; 4. Linkages / networking; 5. Representation and participation. A score of 1 (Poor) to 5 (Good) is assigned for each aspect, leading to an overall score. This score will be used as the indicator of CFR capacity to assess improvement over the project period.